Developing an International Standardized Arabic Language Education Curriculum: Introducing a Conception-Focused Design and Outcome - Yayan Nurbayan; Sofyan Sauri; Anwar Sanusi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2021)
This research aimed to explore the concept of developing an international standard Arabic curriculum in universities. This curriculum development concept focused on curriculum design and graduate profiles. This study used a library research approach. The data analysis technique used the interactive data analysis model proposed by Miles et al including data collection, data reduction, data display, and concluding. The study's results showed that the development of an international standard curriculum viewed consisted of 10 steps, namely research and collection, planning, developing initial products, conducting preliminary tests in the field, revising products, conducting field tests, revising operational products, conducting operational testing in the field, final product revision, and deployment and implementation. Meanwhile, the profile of Arabic education program graduates formulated consisted of three aspects: graduates with competence as teachers, employability skills, and 21st-century skills. Based on the results of this study, it is expected to bring enlightenment and academic horizons to education providers in higher education in developing an international standard Arabic curriculum.